Public acceptance of connected vehicles: An extension of the technology acceptance model. (July 2022) - Acharya, Sailesh; Mekker, Michelle
Highlights: Proposed and validated a novel connected vehicle (CV) acceptance model (CVAM). Perceived data privacy and security (PPS), perceived trust (PT), perceived usefulness (PU), and perceived ease of use (PEOU) were found to be the determinants of CV acceptance. PPS was found to negatively affect CV acceptance directly and indirectly through all other determinants of CV acceptance. PT had a major role in developing positive perception on CV acceptance but its directional relationship with PU and PEOU is unclear. Abstract: To examine the public acceptance of connected vehicles (CVs), this study developed a novel connected vehicle acceptance model (CVAM) extending the technology acceptance model (TAM). The model was built based on a questionnaire survey of 2400 US adults. Perceived data privacy and security associated with the technology was found to shape the trust, attitude, and behavioral intention to use CVs, in addition to the predictors of original TAM: perceived usefulness and ease of use. Results revealed that trust mediates the effect of perceived data privacy and security on CV acceptance, though its directional relationship with perceived usefulness and perceived ease of use is unclear. Socio-demographic and other characteristics of respondents associated with CV acceptance and its predictors were explored. A number of theoretical and practical implications of the study findings are discussed.